2012
DOI: 10.3390/en5041175
|View full text |Cite
|
Sign up to set email alerts
|

A Fuzzy Logic Global Power Management Strategy for Hybrid Electric Vehicles Based on a Permanent Magnet Electric Variable Transmission

Abstract: Abstract:The major contribution of this paper is to propose a Fuzzy Logic Global Power Management Strategy for Hybrid Electric Vehicles (HEVs) that are driven by the PM-EVT (PM machine-Electric Variable Transmission) powertrain, such that the PM-EVT will have superior advantages over other types of powertrains, including the current Toyota Prius powertrain for series-parallel HEVs. This has been investigated throughout three aspects. The first is the optimum power splitting between the Internal Combustion Engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…It can be described as follows: when T m1 > T out1 and T m2 > T out2 , make T m2 = T out2 , then, β may be bigger than the current value according to Equation (2), and the vehicle will still be broken safely based on the braking stability scope (Figure 3), however, the regenerative braking energy recovery efficiency may be limited; when T m1 > T out1 ; T m2 ≤ T out2 or T m1 > T out1 ; T m2 > T out2 , if make T m1 = T out1 , β may be lower than the current value, and the vehicle may be broken unsafely, in which case, the vehicle will be broken according to Condition 1:…”
Section: Predictive Control Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be described as follows: when T m1 > T out1 and T m2 > T out2 , make T m2 = T out2 , then, β may be bigger than the current value according to Equation (2), and the vehicle will still be broken safely based on the braking stability scope (Figure 3), however, the regenerative braking energy recovery efficiency may be limited; when T m1 > T out1 ; T m2 ≤ T out2 or T m1 > T out1 ; T m2 > T out2 , if make T m1 = T out1 , β may be lower than the current value, and the vehicle may be broken unsafely, in which case, the vehicle will be broken according to Condition 1:…”
Section: Predictive Control Modelmentioning
confidence: 99%
“…Transportation consumes a large proportion of energy, and the application of electric vehicles (EVs) has become a global strategy for saving energy and using sustainable energy [1][2][3]. In order to improve the energy efficiency further, regenerative braking and mechanical braking cooperative systems are widely used in EVs.…”
Section: Introductionmentioning
confidence: 99%
“…The dashed arrow lines in the figure indicate the directions of power flows. To guarantee a quick and adequately precise simulation, a quasi-static modeling methodology [21] was used to model the power request of the hybrid powertrain. Table 1 lists the vehicle parameters used in the model.…”
Section: Hybrid Powertrain Modelingmentioning
confidence: 99%
“…Many control strategies, such as fuzzy control, logic threshold control, dynamic programming and artificial neural network control, have been developed and successfully applied in HEVs [2][3][4][5][6][7][8][9][10]. Comparative studies have shown that the flexibility of the control strategies is very important for the improvement of the control effects [2,3]. This paper attempts to achieve an identification of vehicle driving patterns to improve the control flexibility, and eventually improve the fuel economy of HEVs.…”
Section: Introductionmentioning
confidence: 99%
“…Since the powertrain control strategy plays a very important role in improving the performance of HEVs, the study of new control theories that can be applied to the power trains of HEVs is very significant [1,2]. Many control strategies, such as fuzzy control, logic threshold control, dynamic programming and artificial neural network control, have been developed and successfully applied in HEVs [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%